Association of the timing and type of acute symptomatic seizures with poststroke epilepsy and mortality: clinical and population sciences - Schubert, Kai Michael; Zieglgänsberger, Dominik; Bicciato, Giulio; Abraira, Laura; Santamarina, Estevo; Álvarez-Sabín, José; Ferreira-Atuesta, Carolina; Katan, Mira; Sinka, Lucia; Terziev, Robert; Deligas, Nico; Erdélyi-Canavese, Barbara; et al. (Stroke, 2025)
BACKGROUND: - Acute symptomatic seizures (ASyS) increase the risk of epilepsy and mortality after a stroke. The impact of the timing and type of ASyS remains unclear. - METHODS: - This multicenter cohort study included data from 9 centers between 2002 and 2018, with a final analysis in February 2024. The study included 4552 adults (2005 female; median age, 73 years) with ischemic stroke and no seizure history. Seizures were classified using International League Against Epilepsy definitions. We examined ASyS occurring within 7 days after stroke. The main outcomes were all-cause mortality and epilepsy. Validation of the updated SeLECT score (SeLECT-ASyS) was performed in 3 independent cohorts (Switzerland, Argentina, and Japan) collected between 2012 and 2024, including 74 adults with ASyS. - RESULTS: - The 10-year risk of poststroke epilepsy ranged from 41% to 94%, and mortality from 36% to 100%, depending on ASyS type and timing. ASyS on stroke onset day had a higher epilepsy risk (adjusted hazard ratio [aHR], 2.3 [95% CI, 1.3-4.0]; P=0.003) compared with later ASyS. Status epilepticus had the highest epilepsy risk (aHR, 9.6 [95% CI, 3.5-26.7]; P<0.001), followed by focal to bilateral tonic-clonic seizures (aHR, 3.4 [95% CI, 1.9-6.3]; P<0.001). Mortality was higher in those with ASyS presenting as focal to bilateral tonic-clonic seizures on day 0 (aHR, 2.8 [95% CI, 1.4-5.6]; P=0.004) and status epilepticus (aHR, 14.2 [95% CI, 3.5-58.8]; P<0.001). The updated SeLECT-ASyS model, available as an application, outperformed a previous model in the derivation cohort (concordance statistics, 0.68 versus 0.58; P=0.02) and in the validation cohort (0.70 versus 0.50; P=0.18). - CONCLUSIONS: - ASyS timing and type significantly affect epilepsy and mortality risk after stroke, improving epilepsy prediction and guiding patient counseling.
Online veröffentlicht: 24. April 2025
Gesehen am 16.09.2025